Multiple authorship and intermedia revision: an editorial approach to Pedro Homem de Mello's poems adapted to fado - Pereira, Elsa (2017)
This article deals with a few poems by Pedro Homem de Mello (1904-1984) which were adapted to fado song (UNESCO’s Intangible Cultural Heritage of Humanity), as well as a number of textual problems that require consideration of both the author’s and the composer’s work. These challenges, arising from remediation processes, lead me to consider an editorial digital approach, taking into account the specific nature of the materials involved and their various potential uses.